The schizo-obsessive disorder: a case report - Urbańska, Anna; Lis, Agnieszka; Sołowiej, Mateusz; Perzyńska-Starkiewicz, Aneta; Szymczuk, Diana; Olajossy, Marcin (Current Problems of Psychiatry, 2017)
Purpose: A case of schizophrenia with coexisting obsessive-compulsive symptoms is reported.Case: The frequency of obsessive-compulsive disorder (OCD) and obsessive-compulsive symptoms (OCS) occurrence among patients suffering from schizophrenia is considerably higher in comparison to general population. The results of some studies show that schizo-obsessive disorder is characterized by higher intensity of negative and depressive symptoms. Patients with comorbid schizophrenia and obsessive-compulsive disorder show greater level of social dysfunction and they exhibit suicidal behaviours more often than patients diagnosed with schizophrenia. We present a 33-year-old female with obsessive-compulsive symptoms with onset in her early teens with no satisfactory response to treatment, in spite of her good intellect and insight into illness and cooperation.Comment: There is some evidence suggesting that patients with “schizo-obsessive disorder” have a worse prognosis com-pared to the group of patients suffering only from schizophrenia, but the effect of OCD on schizophrenia symptom profile is unclear.